Supervisor Narcissism and Time Theft: Investigating the Mediating Roles of Emotional Exhaustion and the Moderating Roles of Attachment Style - Ding, Zhihui; Liu, Wenxing; Zhang, Guanglei; Wang, Huaqiang (Frontiers in Psychology, 2018)
Although some studies have begun to explore the factors influencing employees’ time theft, it has not been uncommon to link employee time theft to leader personality traits. Based on the conservation of resources theory, this paper examines the influence of supervisor narcissism on employee time theft. It is found that supervisor narcissism positively affects employee time theft via the emotional exhaustion of employees. Further, employee’s attachment styles moderate the mediation effect of emotional exhaustion between supervisor narcissism and employee time theft. This study adds important insights into employee time theft, leader negative traits and the theory and practice of organizational management.